Malnutrition in children under five in Iran - Moridi, G; Fathi, M (Advances in Nursing & Midwifery, 2009)
Background Children make a significant proportion of human population and their healthy growth and development ensure the future health of society. Childhood is considered as one of the most significant life stages for growth and health at other stages. Due to specific nutritional need, children are prone to food insufficiency. Accordingly, nutritional condition of children under 5 is an appropriate measure for evaluating the condition of health in a society. Purpose This study was intended to report malnutrition condition of Iranian children under 5 by reviewing related studies. Methods Different Iranian and international databases including Iran Medex, Irandoc and Pubmed were searched. Results Studies found that the prevalence of malnutrition in children under 5 was different at regions of the country and between 8.6% and 34%. The least amount (8.6%) was seen in Gilan province and the highest in Sistan and Baloochestan province. Risk factors in this regard were low-birth-weight, poor family planning, lack of consumption of complementary food, lack of mother’s knowledge regarding the proper time to start complementary nutrition and low level of mother’s education. Keywords: Malnutrition, Children under five, Nutritional state.